A comprehensive investigation on 3D printing of polyamide 11 and thermoplastic polyurethane via multi jet fusion - Tey, Wei Shian (2021)
Multi Jet Fusion (MJF) is a recently developed polymeric powder bed fusion (PBF) additive manufacturing technique that has received considerable attention in the industrial and scientific community due to its ability to fabricate functional and complex polymeric parts efficiently. In this work, a systematic characterization of the physicochemical properties of MJF-certified polyamide 11 (PA11) and thermoplastic polyurethane (TPU) powder was conducted. The mechanical performance and print quality of the specimens printed using both powders were then evaluated. Both PA11 and TPU powders showed irregular morphology with sharp features and had broad particle size distribution, but such features did not impair their printability significantly. According to the DSC scans, the PA11 specimen exhibited two endothermic peaks, while the TPU specimen exhibited a broad endothermic peak (116-150 °C). The PA11 specimens possessed the highest tensile strength in the Z orientation, as opposed to the TPU specimens which possessed the lowest tensile strength along the same orientation. The flexural properties of the PA11 and TPU specimens displayed a similar anisotropy where the flexural strength was highest in the Z orientation and lowest in the X orientation. The porosity values of both the PA11 and the TPU specimens were observed to be the lowest in the Z orientation and highest in the X orientation, which was the opposite of the trend observed for the flexural strength of the specimens. The PA11 specimen possessed a low coefficient of friction (COF) of 0.13 and wear rate of 8.68 × 10⁻⁵ mm³/Nm as compared to the TPU specimen, which had a COF of 0.55 and wear rate of 0.012 mm³/Nm. The PA11 specimens generally had lower roughness values on their surfaces (Rₐ < 25 μm), while the TPU specimens had much rougher surfaces (Rₐ > 40 μm). This investigation aims to uncover and explain phenomena that are unique to the MJF process of PA11 and TPU while also serving as a benchmark against similar polymeric parts printed using other PBF processes.